Overwintering by the western thatch ant, Formica obscuripes (Hymenoptera, Formicidae) - D. Christian Furness; Elaine Tan; John T. Longino (Contributions to Entomology)
Temperate zone ants overwinter using a variety of mechanisms. The genus Formica overwinters entirely as adults. In at least one species it has been demonstrated that winter workers are more corpulent than summer foragers, storing resources in their bodies and mobilizing them for early brood production in spring. Here we examine overwintering by the common western thatch ant, F. obscuripes. Excavation of a winter nest revealed only workers, distributed in multiple chambers in a roughly spherical region from 0.5 to 1.05 m deep. Worker size, as measured by head width, was weakly bimodal, with fewer workers in the small vs. large size class. We measured dry weights of workers from the winter nest and workers collected the previous summer from the surfaces of multiple nests in the vicinity, including our excavated nest. Controlling for size, there was no evidence of bimodality in winter worker weight, and winter workers were 59.7% heavier than summer foragers. These results suggest that F. obscuripes workers are at their maximum corpulence going into their first winter, expend their stored fat during spring, and mostly die before overwintering a second time. It remains uncertain whether workers can regain corpulence.